1984
DOI: 10.1021/jf00123a026
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidative activity of oxyfluorfen with regard to carotenoids in Scenedesmus

Abstract: of changes in the activities of these enzymes may be known only after detailed analysis for free and protein amino acids, in vivo concentration of different metabolites, particularly in the vicinity of various enzymes, and chasing the fate of labeled NH4+, glutamine, and asparagine. On the basis of the resulte presented, it may, however, be suggested that in developing wheat grain, both the glutamate synthase cycle and the GDH pathway may be operative in ammonia assimilation, the former predominating during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…DUKE et al2,3), ENSMINGER and HESS5), ORR and HESS22) and MATSUNAKA21) demonstrated that photosynthesis was not required for the toxicity of diphenyl ether herbicides. In contrast, KUNERT and BOGER14) and LAMBERT et al 15,16) reported that oxyfluorfen action on unicellular algae Scenedesmus and Bumilleriopus was completely protected by diuron. MATRINGE et al demonstrated that the pyrimidine derivative LS82-556 ((S) 3-N-(methylbenzyl) carbamoyl-5-propionil-2, 6lutidine) which showed peroxidation of cell membrance similar to diphenyl ethers required photosynthesis in the mechanism of action20).…”
Section: Electrolytementioning
confidence: 95%
“…DUKE et al2,3), ENSMINGER and HESS5), ORR and HESS22) and MATSUNAKA21) demonstrated that photosynthesis was not required for the toxicity of diphenyl ether herbicides. In contrast, KUNERT and BOGER14) and LAMBERT et al 15,16) reported that oxyfluorfen action on unicellular algae Scenedesmus and Bumilleriopus was completely protected by diuron. MATRINGE et al demonstrated that the pyrimidine derivative LS82-556 ((S) 3-N-(methylbenzyl) carbamoyl-5-propionil-2, 6lutidine) which showed peroxidation of cell membrance similar to diphenyl ethers required photosynthesis in the mechanism of action20).…”
Section: Electrolytementioning
confidence: 95%